Diapause in field populations of codling moth Cydia pomonella (L.)(Lepidoptera: Tortricidae) under southern Chile conditions - Carrillo, R.=700 1 Astorga, P.; Neira, M.
(Es, En)
Ilus., 14 ref.
Keywords: CYDIA POMONELLA; LEPIDOPTERA; DIAPAUSA; CHILE; REVISTA CHILENA DE ENTOMOLOGIA